Fase Deaktivasi Fermentasi Bioethanol dari Sorgum dengan Beads Biokatalis Ko-Immobilisasi Yeast dan Enzim Glukoamilase Menggunakan Anaerobic Baffled Reactor (ABR) - Pangesti Willistania; Pristiwati Iustitie Poetranto; Mujtahid Kaavessina; Margono Margono (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Bioethanol is one of many promising fuels and alternative energies because bioethanol is made from natural fermentation which can be renewed. White sorgum seed (Shorgum bicolor (L) Moench) is abundantly available in tropical area. With starch content among 70 - 80 wt%, it has the potential as a raw material of bioethanol production. This research is conducted continuously in 4 chambers of Anaerobic Baffled Reactor (ABR) with biocatalyst beads of co-immobilized glucoamylase and yeast (Saccharomycescereviceae) in Na-Alginat. Deactivation time of fermentation can be observed when the decreasing of ethanol content was detected. This time shows the dead phase which is needed in the optimization of bioethanol production by determination of some factors causes this phase. The result showed that the biocatalyst beads began to undergo deactivation in every ABR chambers after 358 hours of the fermentation. At this time, the ethanol content in each chamber is: A 1.828 g/L, B 2,319 g/L, C 2,810 g/L, dan  D 3,019 g/L.